2009
DOI: 10.1590/s0074-02762009000800007
|View full text |Cite
|
Sign up to set email alerts
|

The triatominae species of French Guiana (Heteroptera: Reduviidae)

Abstract: An annotated list of the triatomine species present in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
25
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 20 publications
3
25
0
5
Order By: Relevance
“…For example, Naiff et al (1998) reported only three species (P. geniculatus, R. robustus and R. pictipes) in an urban environment, and Valente et al (2009) collected only two species (R. pictipes and P. geniculatus) in and around a rural settlement. Bérenger et al (2009) reported similar results from French Guiana: 11 triatomine species were collected in forested areas, but only five (P. geniculatus, P. lignarius, R. pictipes, R. robustus, and E. mucronatus) were found in anthropic landscapes.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…For example, Naiff et al (1998) reported only three species (P. geniculatus, R. robustus and R. pictipes) in an urban environment, and Valente et al (2009) collected only two species (R. pictipes and P. geniculatus) in and around a rural settlement. Bérenger et al (2009) reported similar results from French Guiana: 11 triatomine species were collected in forested areas, but only five (P. geniculatus, P. lignarius, R. pictipes, R. robustus, and E. mucronatus) were found in anthropic landscapes.…”
supporting
confidence: 58%
“…The genus Rhodnius was represented by three species. Two of them, Rhodnius robustus and Rhodnius pictipes, are common in Amazonia and have been implicated in Chagas disease transmission (Abad-Franch & Monteiro 2007, Valente et al 2009), whereas Rhodnius amazonicus is a rare species hitherto known only from type specimens and a few additional collections in French Guiana (Bérenger & Pluot-Sigwalt 2002, Bérenger et al 2009). …”
mentioning
confidence: 99%
“…M. trinidadensis was not collected recently. Nonetheless, its presence in Suriname is entirely possible because a specimen was recently found in French Guiana, less than 200 km from Suriname (Bérenger et al 2009). T. maculata was collected in colonial times, but has not been seen found since.…”
Section: Resultsmentioning
confidence: 99%
“…Haematophagous Triatominae, vectors of Chagas disease, are also relatively unknown in the Guianas and investigations into their diversity and distribution in the three countries are scarce (Lent & Wygodzinsky 1979, Bérenger et al 2009). Lent and Wygodzinsky (1979) mentioned the occurrence of Triatoma maculata (Erichson, 1848), Eratyrus mucronatus Stål, 1859, Pans-trongylus geniculatus (Latreille, 1811), Panstrongylus lignarius (Walker, 1873), Rhodnius pictipes Stål, 1872, Rhodnius prolixus Stål, 1859 and Microtriatoma trinidadensis (Lent, 1951) in Suriname.…”
mentioning
confidence: 99%
“…Thus, Rhodnius milesi ( Valente et al 2001 ) is probably a Rhodnius neglectus variant from south-eastern Amazonia, Rhodnius zeledoni ( Jurberg et al 2009 ) closely resembles Rhodnius domesticus , and Rhodnius montenegrensis ( da Rosa et al 2012 ) likely represents one of the R. robustus lineages of Monteiro et al (2003) . Furthermore, some Rhodnius species, such as Rhodnius dalessandroi , Rhodnius paraensis or Rhodnius amazonicus , have seldom been collected; their ecological-evolutionary characteristics and affiliations remain therefore unclear ( Barrett 1991 , Abad-Franch et al 2009 , Bérenger et al 2009 ).…”
mentioning
confidence: 99%